Dari Sungai Medang untuk Dunia: Kolaborasi Masyarakat dalam Menjadikan Air Terjun Ikonik Kerinci sebagai Destinasi Ekowisata Unggulan: Pengabdian - Liona Efrina. S; Eka Julianti Efris Saputri; Parassela Pangestu Primadiva; Vera Amalia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sungai Medang Waterfall is not just a natural tourist attraction, but also a Sungai Medang Waterfall is not only a natural tourist attraction, but also a great potential that can be developed as an ecotourism destination based on local wisdom. Despite its extraordinary appeal, the local community faces serious challenges, especially related to minimal understanding of sustainable tourism management, promotion, and packaging of local attractions. This community service activity aims to increase the capacity of the community to manage tourism potential independently. The approach used includes training, mentoring, and the preparation of a structured tourism development plan. The implementation methods applied include field observation, Focus Group Discussion (FGD), tourism management training, and the creation of promotional media. The results of this activity show an increase in community understanding of the concept of ecotourism, as well as the preparation of an action plan for developing Sungai Medang Waterfall tourism. The conclusion of this activity emphasizes the importance of collaboration between the community, village government, and academics in realizing a sustainable tourism destination that is not only economically profitable, but also preserves culture and the environment.